Enhancing and accelerating stroke treatment in Eastern European region: Methods and achievement of the ESO EAST program - Mikulík, Robert; Caso, Valeria; Bornstein, Natan M; Svobodová, Veronika; Pezzella, Francesca Romana; Grecu, Andreea; Simsic, Steven; Gdovinova, Zuzana; Członkowska, Anna; Mishchenko, Tamara S; Flomin, Yuriy; Milanov, Ivan G; et al. (European stroke journal, 2020)
INTRODUCTION: Despite the availability of prevention and therapies of stroke, their implementation in clinical practice, even of low-cost ones, remains poor. In 2015, the European Stroke Organisation (ESO) initiated the ESO Enhancing and Accelerating Stroke Treatment (EAST) program, which aims to improve stroke care quality, primarily in Eastern Europe. Here, we describe its methods and milestones. PATIENTS AND METHODS: The ESO EAST program is using an implementation strategy based on a 'detecting-understanding-reducing disparities' conceptual framework: stroke care quality is first measured (after developing a platform for data collection), gaps are identified in the current service delivery, and ultimately feedback is provided to participating hospitals, followed by the application of interventions to reduce disparities. The ESO EAST program is carried out by establishing a stroke quality registry, stroke management infrastructure, and creating education and training opportunities for healthcare professionals. RESULTS: Program management and leadership infrastructure has been established in 19 countries (Country Representatives in 22 countries, National Steering Committee in 19 countries). A software platform for data collection and analysis: Registry of Stroke Care Quality was developed, and launched in 2016, and has been used to collect data from over 90,000 patients from >750 hospitals and 56 countries between September 2016 and May 2019. Training in thrombolysis, nursing and research skills has been initiated. DISCUSSION: ESO EAST is the first pan-Eastern European (and beyond) multifaceted quality improvement intervention putting evidence-informed policies into practice. Continuous monitoring of stroke care quality allows hospital-to-hospital and country-to-country benchmarking and identification of the gaps and needs in health care.
Keywords: clinical audit; Stroke; implementation; quality indicators; registry